ECOWAS's Infrastructure : A Regional Perspective - Ranganathan, Rupa (2012)
Infrastructure improvements boosted growth in the Economic Community of West African States (ECOWAS) by one percentage point per capita per year during 1995-2005, primarily thanks to growth in information and communication technology. Deficient power infrastructure held growth back by 0.1 percent. Raising the region's infrastructure to the level of Mauritius could boost growth by 5 percentage points. Overall, infrastructure in the 15 ECOWAS countries ranks consistently behind southern Africa across many indicators. However, there is parity in access to household services -- water, sanitation, and power. ECOWAS has a well-developed regional road network, though sea corridors and ports need attention. Surface transport is expensive and slow, owing to cartelization, restrictive regulations, and delays. There is no regional rail network. Air transport has improved despite the lack of a strong hub-and-spoke structure. Safety remains a concern. Electrical power, the most expensive and least reliable in Africa, reaches 50 percent of the population but meets just 30 percent of demand. Regional power trading would bring substantial benefits if Guinea could become a hydropower exporter. Prices for critical ICT services are relatively high. Recent panregional initiatives have improved roaming. New projects are underway to provide access and improved services to unconnected countries. Completing and maintaining ECOWAS's infrastructure will require sustained spending of $1.5 billion annually for a decade, with one-third going to power. Although the necessary spending is only 1 percent of regional GDP, some countries' share is between 5 and 25 percent of national GDP. Clearly, external assistance will be needed.